PEMANFAATAN LIMBAH KORAN DAN ABU TERBANG SEBAGAI BAHAN CAMPURAN DINDING PANEL DENGAN PERKUATAN WIRE MESH - Mochammad Nur Huda; Mochamad Teguh (TEKNISIA, 2018)
In general, Construction used a bricks, concrete bricks, or hebel as one of the wall materials.  One another alternative is the panel wall. The panel wall is a unit of severals concrete blocks and it arranged in such a way that it becomes a wall. The purpose of this study was to determine the strength of the wall panels made of papercrete. The wall panel of the papercrete can be obtained by mixing pulp, fly ash, and sand with cement paste as an adhesive material and then manually printed on a formwork with a sample in the form of cubes with a size (555) cm3 for concrete paper testing. Whereas in the wall sample, in the form of beam size (50505) cm3 for the test of compressive strength, size (100505) cm3 for flexural test, and size (1201205) cm3 for diagonal shear test. The composition used (Portland Cement : Sand : Paper : Fly ash) is (1:3:0,25:0), (1:3:0,25:0,2), (1:3 0,5:0,2), (1:3:0 ,5:0,4). Each wall sample was given reinforcement in the form of wire mesh with 2 types of placement, namely a single wire located in the middle of the span and two wires installed between the layer of the papercrete span. From the test results obtained an average volume weight ranged from 1,965 to 2,068 grams / cm3, with the highest papercrete compressive strength in the sample (1:3:0,25:0,2) of 15,619 MPa. In wall testing, the highest compressive strength was found in samples with single wire mesh reinforcement with an average of 12,31 MPa. The highest flexural strength in the sample with double wire mesh reinforcement of 3,573 MPa. In the diagonal shear strength test the highest results were obtained in the sample with a double wire mesh reinforcement of 2,587 MPa.